Phytoextraction of copper from a contaminated soil using arable and vegetable crops. (March 2019) - Napoli, Marco; Cecchi, Stefano; Grassi, Chiara; Baldi, Ada; Zanchi, Camillo A.; Orlandini, Simone
Abstract: Copper (Cu) is among the main contaminant of agricultural soil. The reclamation of Cu polluted soils can be achieved with phytoextraction even if, in general, plants are Cu-excluders and uncommon are Cu-accumulators. The research objectives were to establish the Cu removal capacity by arable and vegetable crops and to investigate the distribution of Cu in their roots, stems and leaves, and fruits. Pot trials were conducted for two subsequent years in Tuscany (Italy). Cu was added into soil in four levels (0, 200, 400, 600 mg kg −1 of Cu). At harvesting, the crops roots, stems and leaves, and fruits or seeds were separately collected, oven dried, weighted, milled and separately analyzed. The results show that the GDUs value to reach the physiological maturity for barley, common bean, Indian mustard, and ricinus was significantly positively correlated with Cu concentration in soil in contrast with observed in sorghum, spinach, and tomato. Leaves and stems of spinach and ricinus have a good storage capacity in contrast with common bean, tomato, Indian mustard sorghum and barley. Tomato storage Cu mainly in fruits and roots which show a remarkable concentration of Cu that increases progressively with the increase of Cu concentration in the soil. In addition, the roots of common bean and ricinus showed a very high concentration of Cu. All species can be considered Cu-excluders because of their low capacity to uptake high quantity of Cu. Indian mustard can be considered a plant able to translocate the metal from root to epigeal tissue. Highlights: Arable and vegetable crops showed different response to copper concentration. Copper concentration was determined in different tissues of crops. Arable and vegetable crops had not stored copper above the safety standards.